2010
DOI: 10.5688/aj740699
|View full text |Cite
|
Sign up to set email alerts
|

A Team Public Health Research Project for First-Year Pharmacy Students to Apply Content From Didactic Courses

Abstract: Objectives. To implement and assess a first-year pharmacy student group research project that provided practical hands-on application and reinforced the curricula of concurrent didactic courses. Design. Groups of 6 to 7 students chose a public health topic based on the Healthy People 2010 Priority Areas and created a survey instrument. Faculty facilitated mock institutional review board (IRB) review sessions which provided teams with ongoing feedback and refinement recommendations before each team administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 9 publications
(9 reference statements)
0
12
0
Order By: Relevance
“…These have included a semester-long systems course for first-year students, 28 skills-based laboratory for secondyear students, 29 problem-based learning in a clinical therapy course, 30 semester-long elective including a 1-week simulation for second-and third-year students, 31 simulation during a clinical assessment course for third-year American Journal of Pharmaceutical Education 2012; 76 (10) Article 203. students, 32 lecture and case-based role-play for third-year students, 33 service-learning at a children's diabetes mellitus camp for fourth-year students, 34 and a 1-day simulation for pharmacy managers (postgraduate education). 35 While several of these educational efforts have listed "development of empathy for diabetes mellitus patients" as a learning objective, few have successfully quantified achievement.…”
mentioning
confidence: 99%
“…These have included a semester-long systems course for first-year students, 28 skills-based laboratory for secondyear students, 29 problem-based learning in a clinical therapy course, 30 semester-long elective including a 1-week simulation for second-and third-year students, 31 simulation during a clinical assessment course for third-year American Journal of Pharmaceutical Education 2012; 76 (10) Article 203. students, 32 lecture and case-based role-play for third-year students, 33 service-learning at a children's diabetes mellitus camp for fourth-year students, 34 and a 1-day simulation for pharmacy managers (postgraduate education). 35 While several of these educational efforts have listed "development of empathy for diabetes mellitus patients" as a learning objective, few have successfully quantified achievement.…”
mentioning
confidence: 99%
“…24,25 The characteristics of student research programs included in the systematic review are shown in Table 1. There were three reports [26][27][28] (25%) of elective student research programs, one report of a student research track 29 (8%), and eight reports 24,[30][31][32][33][34][35][36] (67%) of required student research programs. The elective student research programs involved relatively few students (the number ranged from 7 to 25) and the types of research projects were limited to primarily bench science and clinical studies.…”
Section: Resultsmentioning
confidence: 99%
“…The one research track offered was more similar to the elective student research programs than to the required programs; only two types of research were offered, bench science and practice issues, and only 20 students participated at a time. 29 In the eight required research programs, 24,[30][31][32][33][34][35][36] reported class sizes ranged from 50 to 210. Only two programs 33,34 required students to work individually; other programs allowed students to work in groups of one to seven students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, pharmacy student training to work collaboratively with other health professionals is minimal in most colleges and schools. Public health and health promotion concepts are incorporated in some novel pharmacy curricula, 21,22 but the use of interprofessional learning concepts to emphasize that health promotion and health education is a role shared by all health professionals is minimal.…”
Section: Introductionmentioning
confidence: 99%